Oral potentially malignant disorder research in Taiwan and mainland China: A scientometric analysis - Wei Liu; Yinhui Yang; Xinyu Zhang; Huan Shi (Elsevier, 2022)
Scientometric analysis of a disease is often conducted to recognize research trends and study hotspots. In this report, we analyze the scientometric characteristics of oral potentially malignant disorder (OPMD) research in Taiwan and mainland China. There are 324 and 718 articles on OPMD research originating from Taiwan and Mainland between 2006 and 2021, respectively. The most common subtype of OPMD research in Taiwan and Mainland is oral submucous fibrosis and lichen planus, respectively. Based on the list of main keywords extracted from the included articles, areca/betel quid chewing and alcohol use are the distinctive risk factors in Taiwan. Research on cancer screening, fibroblast/myofibroblast, and smooth muscle actin α are distinctive keywords in Taiwan; whereas the research on apoptosis, cytokine, and inflammation are distinctive keywords in Mainland. The distinctive characteristics of OPMD research are analyzed between Taiwan and mainland China, which may reflect the importance and concerned topics of research.